2017
DOI: 10.1039/c6cc08305f
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence for origins of size and support effects on selectivity of Cu nanoparticle dehydrogenation catalysts

Abstract: Selective dehydrogenation catalysts that produce acetaldehyde from bio-derived ethanol can increase the efficiency of subsequent processes such as C-C coupling over metal oxides to produce 1-butanol or 1,3-butadiene or oxidation to acetic acid. Here, we use in situ X-ray absorption spectroscopy and steady state kinetics experiments to identify Cu at the perimeter of supported Cu clusters as the active site for esterification and Cu surface sites as sites for dehydrogenation. Correlation of dehydrogenation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15]. Among these catalysts, Cu-based catalysts exhibit very high activity and good selectivity toward acetaldehyde, in part, because Cu can cleave C-C and C-O bonds at much lower rates than other transition metals (e.g., Pd and Pt) [16]. However, a rapid deactivation due to Cu particle sintering often occurs on Cu-based catalysts [12,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11][12][13][14][15]. Among these catalysts, Cu-based catalysts exhibit very high activity and good selectivity toward acetaldehyde, in part, because Cu can cleave C-C and C-O bonds at much lower rates than other transition metals (e.g., Pd and Pt) [16]. However, a rapid deactivation due to Cu particle sintering often occurs on Cu-based catalysts [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…Some inert substances that inhibit Cu sintering have been widely used as textural promoters, and amphoteric or basic metal oxides have been proven to be beneficial for improving the dehydrogenation activity [18][19][20][21]. In addition, the effects of the Cu content and the chemical state of the active Cu species on the catalytic activity have also been investigated [16,[22][23][24][25][26][27]. Bueno et al [22] found that the selectivity for the products was related to the metal dispersion defined by the Cu content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper‐supported on porous SiO 2 are currently the most efficient catalysts . However, undesired side reactions, such as esterification, aldol condensation, and ketonization, often occur and lower the selectivity of this reaction (<80%). It has been an agreement that exposed Cu 0 can catalyze the dehydrogenation of ethanol, while Cu δ+ and Si‐OH often accelerates secondary reactions ,.…”
Section: Introductionmentioning
confidence: 99%
“…However, undesired side reactions, such as esterification, aldol condensation, and ketonization, often occur and lower the selectivity of this reaction (<80%). It has been an agreement that exposed Cu 0 can catalyze the dehydrogenation of ethanol, while Cu δ+ and Si‐OH often accelerates secondary reactions ,. These undesired Cu δ+ sites are generated during reduction pretreatment, which are unavoidable for Cu/SiO 2 catalysts due to the strong interaction between Cu nanoparticles and SiO 2 ,.…”
Section: Introductionmentioning
confidence: 99%